Agricultural research and poverty reduction - Hazell, Peter B. R.; Haddad, Lawrence J. (International Food Policy Research Institute, 2001)
The primary goal of agricultural research has been to increase agricultural production, particularly in high-potential areas. This has contributed enormously to reducing the number of people living in poverty worldwide, as well as to reducing food prices for all. Despite these gains, about 1 billion rural people still live in poverty in the developing world. In an era in which global food supplies are plentiful though poorly distributed and trade barriers are being reduced, the public sector has a greater opportunity to focus more resources on research strategies that directly benefit the poor. This opportunity is enhanced by the private sector’s increasing role in addressing many mainstream productivity challenges at the global level. But what strategies should the public sector adopt if it is to more explicitly address the needs of the poor? Six key topics for pro-poor agricultural research agendas are described by the authors.